2021
DOI: 10.29128/geomatik.651702
|View full text |Cite
|
Sign up to set email alerts
|

Thornthwaite İklim Sınıflandırma Yöntemine Göre Karadeniz Bölgesi İklim Sınır Haritasının CBS İle Üretilmesi

Abstract: Climate boundary map Thornthwaite climate classification method GIS Kriging interpolation method Black Sea RegionTo know the climate characteristics allows the determination of borders with different climate types; this is important in terms of ensuring the sustainable use of regional resources and direction of land use plans. The determination of climatic boundaries may also serve as a basis for determining and preventing the effects of climate on property and addressing the use of property on a more planned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…It differs from other interpolation methods because it measures the confidence level of the estimated value with variance. This method achieves more unbiased results than other interpolation techniques; investigates the accuracy of the estimation in terms of the minimum variance and the calculation of the standard deviation of the realized estimation [53][54][55].…”
Section: Kriging Interpolation Methodsmentioning
confidence: 99%
“…It differs from other interpolation methods because it measures the confidence level of the estimated value with variance. This method achieves more unbiased results than other interpolation techniques; investigates the accuracy of the estimation in terms of the minimum variance and the calculation of the standard deviation of the realized estimation [53][54][55].…”
Section: Kriging Interpolation Methodsmentioning
confidence: 99%
“…The spatial relationship of these data with the meteorological station points was then established. Although the Thornthwaite and Aydeniz algorithms were included in the developed interface model, they were not included in the results in this study because another study had previously reported on the Thornthwaite method (Colak and Memisoglu, 2021) and the map resulting from the Aydeniz method was not produced with real data and, therefore, could not be tested over the interface model. The parameters determined for the other methods were obtained in line with the inter-agency correspondence of the General Directorate of Meteorology with the relevant institutions in the form of data recorded from 13 meteorological stations over the 30-year period between 1988 and 2018.…”
Section: Methodsmentioning
confidence: 99%